Power electronics power semiconductors, converters and applications - Mohd. Najib Mohd. Hussain; Noor Azila Ismail (Penerbit Universiti Teknologi Mara, 2014)
[This book] presents the fundamentals of power electronics which focuses on power semiconductors, converters and applications.